Rancang Bangun Sistem Informasi Kenaikan Pangkat Dosen Di Jurusan Teknik Elektro Universitas Riau - Azzuhri Azzuhri; Salhazan Nasution (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
At a university, both public and private, of course, there are lecturers for the implementation of the teaching and learning process. lecturers can be declared as professional educators and scientists who have the main task of transforming, developing, and disseminating science, technology, and art through education, research, and community service. Promotion is an award given for the work performance and dedication of lecturers, as well as an encouragement to lecturers to further improve their work performance and dedication. With this promotion, it is intended that the lecturer is able to increase the level of productivity, have more motivation, to do things that are innovative or at least will not violate the existing rules in the agency. Therefore, to take advantage of increasingly advanced technology, we designed a web-based lecturer promotion information system that can assist in the process of lecturer promotion. The testing method used in this study is blackbox testing. Keywords: Lecturer promotion, Information system, Web-based